Influences on the effectiveness of the National Population and Family Development Board's parenting module - K. Doshi, Anjli Panalal; Baharudin, Rozumah (Universiti Putra Malaysia Press, 1999)
The general purpose of this study was to determine the influences on the effectiveness of the National Population and Family Development Board's ( PFDB) parenting module among parents by examining the effects of individual differences (expressed readiness for parenting change and perceptions of parenting self-efficacy) and exposure to the module on parenting knowledge, attitudes, practices, and skills (KAPS) and perceptions of the module. The Pre-testPost-test Control Group Design was used for evaluating the parenting module. A total of 80 respondents were randomly assigned to the experimental and control groups. Results of the study showed that parenting KAPS improved significantly for the experimental group after exposure to the module. Generally, it was found that the participants had high perceptions of the module structure and its usefulness. Results also showed that individual differences was significantly related to parenting knowledge (1'=0.56, p<0.05) and parenting attitudes (1'= 0.46, p<0.05). However, there was no significant correlation between individual differences and parenting practices and skills. Results obtained suggested that exposure to the module was significantly and positively correlated with parenting knowledge (r=0.57, p<0.05), parenting attitudes (r=0.56, p<0.05), parenting practices (r=0.34, p<0.05) and parenting skills (r=0.26, p<0.05). The participants' exposure to the parenting module and individual differences were found to have direct effect on their parenting KAP. The study however, found no evidence to conclude that exposure to the module and individual differences had an effect on the parenting skills of the participants. Nevertheless, on the whole the study concluded that the parenting module was effective in changing the parenting KAPS of parents.